The effect of prolactin on immune cell subsets involved in SLE pathogenesis - Legorreta-Haquet, Maria Victoria; Santana-Sánchez, Paola; Chávez-Sánchez, Luis; Chávez-Rueda, Adriana Karina (Frontiers in Immunology, 2022)
Abstract The higher frequency of autoimmune diseases in the female population compared to males suggests that certain hormones, such as prolactin (PRL), play a role in determining the prevalence of autoimmunity in women, particularly during childbearing age. PRL can act not only as a hormone but also as a cytokine, being able to modulate immune responses. Hyperprolactinemia has been implicated in the pathogenesis of various autoimmune diseases where it may affect disease activity. One of the conditions where PRL has such a role is systemic lupus erythematosus (SLE). PRL regulates the proliferation and survival of both lymphoid and myeloid cells. It also affects the selection of T-cell repertoires by influencing the thymic microenvironment. In autoimmune conditions, PRL interferes with the activity of regulatory T cells. It also influences B cell tolerance by lowering the activation threshold of anergic B cells. The production of CD40 L and cytokines, such as interleukin (IL)-6, are also promoted by PRL. This, in turn, leads to the production of autoantibodies, one of the hallmarks of SLE. PRL increases the cytotoxic activity of T lymphocytes and the secretion of proinflammatory cytokines. The production of proinflammatory cytokines, particularly those belonging to the type 1 interferon (IFN) family, is part of the SLE characteristic genetic signature. PRL also participates in the maturation and differentiation of dendritic cells, promoting the presentation of autoantigens and high IFNα secretion. It also affects neutrophil function and the production of neutrophil traps. Macrophages and dendritic cells can also be affected by PRL, linking this molecule to the abnormal behavior of both innate and adaptive immune responses. This review aimed to highlight the importance of PRL and its actions on the cells of innate and adaptive immune responses. Additionally, by elucidating the role of PRL in SLE etiopathogenesis, this work will contribute to a better understanding of the factors involved in SLE development and regulation.